2013
DOI: 10.1371/journal.pone.0083158
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of Bacterial Species in Plaque from Client Owned Dogs with Healthy Gingiva, Gingivitis or Mild Periodontitis

Abstract: Periodontal disease is the most widespread oral disease in dogs which if left untreated results in significant pain to the pet and loss of dentition. The objective of this study was to identify bacterial species in canine plaque that are significantly associated with health, gingivitis and mild periodontitis (<25% attachment loss). In this survey subgingival plaque samples were collected from 223 dogs with healthy gingiva, gingivitis and mild periodontitis with 72 to 77 samples per health status. DNA was extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
156
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(185 citation statements)
references
References 28 publications
16
156
3
2
Order By: Relevance
“…P. gingivalis, isolated from the human oral cavity, was reported to be a key pathogen in human periodontal disease (Hajishengallis et al, 2012), whereas P. gulae was reported to be the most relevant pathogen in feline periodontal disease (Perez-Salcedo et al, 2012) and has been isolated from gingivitis and mild periodontitis lesions in dogs (Davis et al, 2013) and a case of suppurative otitis and ascending meningoencephalitis in a captive Parma wallaby showing neurological signs (Giannitti et al, 2014).…”
mentioning
confidence: 99%
“…P. gingivalis, isolated from the human oral cavity, was reported to be a key pathogen in human periodontal disease (Hajishengallis et al, 2012), whereas P. gulae was reported to be the most relevant pathogen in feline periodontal disease (Perez-Salcedo et al, 2012) and has been isolated from gingivitis and mild periodontitis lesions in dogs (Davis et al, 2013) and a case of suppurative otitis and ascending meningoencephalitis in a captive Parma wallaby showing neurological signs (Giannitti et al, 2014).…”
mentioning
confidence: 99%
“…3), especially in dogs which showed a higher prevalence than cats. The most prevalent taxon in the phylum Euryarchaeota was the genus Methanobrevibacter, not withstanding that several previous studies did not report the presence of archaea in oral samples and plaque from both dogs and cats [12,[27][28][29] .…”
Section: Discussionmentioning
confidence: 89%
“…The dog oral microbiome has been the subject of several studies using pyrosequencing and cloning, which exhibited a difference in the most abundant phyla between oral samples (oral cavity, buccal site, palatal site and the subgingival pouch) and plaque [12,[27][28][29] . Studies by Sturgeon et al [12] and Oh et al [29] demonstrated that the most abundant bacteria in oral samples were members of the phyla Bacteroidetes or Proteobacteria, respectively, whereas Dewhirst et al [27] and Davis et al [28] found that the phylum Firmicutes was the most prevalent in canine plaque, similar to canine calculus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations